CtIP interacts with TopBP1 and Nbs1 in the response to double-stranded DNA breaks (DSBs) in Xenopus egg extracts - Ramírez-Lugo, Juan S (Landes Bioscience, 2011)
In the presence of double-stranded DNA breaks (DSBs), the activation of ATR is achieved by the ability of ATM to phosphorylate TopBP1 on serine 1131, which leads to an enhancement of the interaction between ATR and TopBP1. In Xenopus egg extracts, the Mre11-Rad50-Nbs1 (MRN) complex is additionally required to bridge ATM and TopBP1 together. In this report, we show that CtIP, which is recruited to DSB-containing chromatin, interacts with both TopBP1 and Nbs1 in a damage-dependent manner. An N-terminal region containing the first two BRCT repeats of TopBP1 is essential for the interaction with CtIP. Furthermore, two distinct regions in the N-terminus of CtIP participate in establishing the association between CtIP and TopBP1. The first region includes two adjacent putative ATM/ATR phosphorylation sites on serines 273 and 275. Secondly, binding is diminished when an MRN-binding region spanning residues 25–48 is deleted, indicative of a role for the MRN complex in mediating this interaction. This was further evidenced by a decrease in the interaction between CtIP and TopBP1 in Nbs1-depleted extracts and a reciprocal decrease in the binding of Nbs1 to TopBP1 in the absence of CtIP, suggestive of the formation of a complex containing CtIP, TopBP1 and the MRN complex. When CtIP is immunodepleted from egg extracts, the activation of the response to DSBs is compromised and the levels of ATR, TopBP1 and Nbs1 on damaged chromatin are reduced. Thus, CtIP interacts with TopBP1 in a damage-stimulated, MRN-dependent manner during the activation of ATR in response to DSBs.